Análise do comportamento dos perfis de raio Gama, potencial espontâneo e eletroresistividade para determinação das zonas aquíferos em poços tubulares - (:unkn) unknown (Universidade Federal do Amazonas, 2006)
Geophysical approaches are used for map and identify structures (fractures and for layers aquifers optimizing the water wells projects elaboration. Among the diverse existing approaches, to resistivity electric, the range radiation emission and the potential spontaneos of the rocky formations are utilized in the determination of the filter sections of water wells in areas you will consolidate. This researches had for objective perform comparative studies of the lines of the geophysical profiles of resistivity eletrical, spontaneous potential and rays range with the main purpose of research to cause that justified the fact of that, in practically all the profile geophysical that utilize these three approaches, there are operative unknown factors that chewed the line of the geophysical profile, of way such that the configuration of this draw, results expected, having like base the theoretical conceptualization. They were utilized samples of components and fluid, the which were analyzed by difratometry of rays x and the results obtained verified it influences of the fluid utilized in the drilling of wells as regards the behavior of the geophysical profiles of electricity, spontaneous potential and rays range.
Keywords: Perfis geofísicos de resistividade; Perfis de raio Gama; Fluidos de perfuração; Difratomentria de raios X; Geophysical approaches; Zonas aquíferas; Difratometry of rays X; Poços tubulares; CIÊNCIAS EXATAS E DA TERRA: GEOCIÊNCIAS